Improving Student’s Vocabulary Ability Through Talking Stick Technique At Grade VIIA Of SMPN 3 Tongauna - Iin Wahyudi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
This research study investigated a study about improving student’s vocabulary ability through talking stick technique at grade VIIA of SMPN 3 Tongauna. The objective of the study was to find out whether talking stick method can improve students’ vocabulary ability. This research applied classroom action research design. Focus on four steps, namely planning, action, observation and reflection. The subject of was students grade VIIA of SMPN 3 Tongauna with the total number of students was 30, consisted 12 females and 18 males. This research was conducted temporary in two cycles where each cycles consist of one meeting of treatment and one meeting for evaluation. This research also implemented vocabulary test (qualitative) and observation sheet (quantitative) as the data of the research. The expected target of students‘ vocabulary ability was 80% the students got standard score 65. Based on the result of this study, it showed that there was an improvement of students’ vocabulary ability at grade VILA of SMPN 3 TONGAUNA the result in the pre-observation 1453 (20%) or 6 students improved, next in the cycle I, there was only 2032 (60%)or 18 students improved. Those are reflected an improved to the next cycle. In the cycle H there researcher found that was more progress than in previous cycle. The percentage of students vocabulary achievement in second cycle was 2359 (87%) or 26 students improved, the result of post test was 2372 (90%) or 27 students improved. Which the vocabulary of students is very good categories. Because the target plan was achieved. There for the treatment stopped based on the result of data it can be conclude that talking stick technique could improve students’ vocabulary ability.